Standing together at the helm - how employees experience employee-driven innovation in primary care - Sarah Samuelson; Sandra Pennbrant; Ann Svensson; Irene Svenningsson (BMC, 2024)
Abstract Primary care needs to find strategies to deal with today's societal challenges and continue to deliver efficient and high-quality care. Employee-driven innovation is increasingly gaining ground as an accessible pathway to developing successful and sustainable organisations. This type of innovation is characterised by employees being engaged in the innovation process, based on a bottom-up approach. This qualitative study explores employees' experiences of employee-driven innovation at a primary care centre in Sweden. Data are collected by focus group interviews and analysed by inductive qualitative content analysis. The result is presented with the overarching theme "Standing together at the helm" followed by three categories: "Motivating factors for practising employee-driven innovation", "Challenges in practising employee-driven innovation" and "Benefits of employee-driven innovation", including nine subcategories. The study found that employee-driven innovation fosters organisational innovation, empowers employees, and enhances adaptability at personal and organisational levels. This enables individual and collective learning, and facilitates the shaping, development, and adaptation of working methods to meet internal and external requirements. However, new employees encountered difficulty grasping the concept of employee-driven innovation and recognising its long-term advantages. Additionally, the demanding and task-focused environment within primary care posed challenges in sustaining efforts in innovation work. The employees also experienced a lack of external support to drive and implement some innovative ideas.